BMI, Physical Activity, Sleep Quality, Eating Attitudes, Emotions: Which One is Affected by Mindful Eating? BMI, Physical Activity, Mindful Eating - Köse, Gizem; Tayfur, Muhittin (Progress in Nutrition, 2021)
Present study, it was aimed to examine the eating attitude and mindful eating status of students and to examine the change of mindful eating status’ besides informing with nutrition course. The study was executed by 318 healthy students aged 18-45 years, randomly selected among students studying at Uskudar University between September 2015 and May 2016. In addition to a survey form containing personal and health information of the students, the Eating Attitudes Test (EAT-40) was conducted by Savasir and Erol, and the Mindful Eating Questionnare-30 (MEQ-30) scale conducted by Turkish Kose et al. The mean age of the participants was 21.56 ± 3.82 year. The mean score of the participants’ EAT-40 score was found to be 24.22 ± 13.98 and the mean score of the MEQ was 98.11 ± 13.81. As the EAT-40 scores decreased, MEQ scores increased, but this relationship was not statistically significant (p> 0.05). It has been shown that 28.9% of students have an eating disorder risk. There was no statistically significant difference between men’s (23.33 ± 15.60) and women’s (24.48 ± 13.50) mean EAT-40 scores (p>0.05). Overweight-obese group was found to be having higher EAT-40 scores than the other BMI classes (p <0.05). While the students’ body weight and BMI increased, the risk of eating disorder increased (r = 0.112, p <0.05 and r = 0.139, p <0.05), and mindful eating decreased (p> 0.05). A significant relationship was found between weight, BMI and MEQ subscales (r =-0.252, p <0.01 and r =-0.208, p<0.01). As food preferences evaluated, 33.3% of students that is vegan, 26.4% of the students that have no food preference and 24.1% of the students that don’t eat red meat were at risk of eating disorder (p <0.05). There was no statistically significant difference between the EAT-40 score groups according to walking status of the participants (p> 0.05). There was a statistically significant relationship between walking status and emotional eating that is one of MEQ subscales (r = -0.159, p <0.01). As having nutrition course, EAT-40 score decreased and the score of MEQ increased (p> 0.05). There was no statistically significant relationship between the level of taking the course and EAT-40, MEQ or the sub-scales of MEQ (p> 0.05). In sum, nutrition courses influence students’ eating attitudes and mindful eating positively. In addition, gaining mindfulness of eating will be helping manage to weight status.